(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background : Urolithiasis is one of the oldest disease known to human beings and has been documented in ancient Greek. Urolithiasis continues to pose a significant health hazard, causing progressive renal impairment, if left untreated. The etiology of renal insufficiency in patients with nephrolithiasis is multifactorial and includes renal obstruction, urinary infection, frequent surgical interventions, and coexisting medical diseases. The purpose of this study is to assess the change in renal function following removal of kidney stones by Percutaneous Nephrolithotomy (PCNL) in patients with associated impaired renal function. Materials and methods : 50 Patients with renal stone disease with associated impaired renal function who were admitted and underwent PCNL in Urology department were selected as per inclusion and exclusion criteria by purposive sampling. Complete clinical evaluation including history, physical examination, relevant examinations & laboratory investigations were performed. All the patients were treated by PCNL monotherapy with Double J stenting. Mean age was 46.63±11.95 years (Age range: 24-72 years). There were 36 males (72%) & 14 females (28%) & male to female ratio was 2.57:1. Results : In this study, a significant fall in mean serum creatinine (0.5 mg%) was demonstrated following the stone removal. The creatinine value remained unchanged in 12% and improved in 84% patients. In contrast to the improvement of renal function as evident by a decline in the mean serum creatinine values, the mean Glomerular Filtration Rate (GFR) registered a small fall of 1.78 ml/min (Statistically not significant). we have observed that total 12 (24%) patients out of 50 cases experienced different sorts of complications. Conclusion: This study showed that PCNL approach to urolithiasis in patients with impaired renal function significantly improves renal functional status manifested according to the preoperative and postoperative difference of serum creatinine and 99mTc DTPA performance. JCMCTA 2019 ; 30 (2) : 70-74